De novo assembly of transcriptomes, mining, and development of novel EST-SSR markers in Curcuma alismatifolia (Zingiberaceae family) through Illumina sequencing - Taheri, Sima; Abdullah, Thohirah Lee; Rafii, M.Y.; Harikrishna, Jennifer Ann; Werbrouck, Stefaan P.O.; Teo, Chee How; Sahebi, Mahbod; Azizi, Parisa (Nature Research, 2019)
Curcuma alismatifolia widely used as an ornamental plant in Thailand and Cambodia. This species of herbaceous perennial from the Zingiberaceae family, includes cultivars with a wide range of colours and long postharvest life, and is used as an ornamental cut flower, as a potted plant, and in exterior landscapes. For further genetic improvement, however, little genomic information and no specific molecular markers are available. The present study used Illumina sequencing and de novo transcriptome assembly of two C. alismatifolia cvs, ‘Chiang Mai Pink’ and ‘UB Snow 701’, to develop simple sequence repeat markers for genetic diversity studies. After de novo assembly, 62,105 unigenes were generated and 48,813 (78.60%) showed significant similarities versus six functional protein databases. In addition, 9,351 expressed sequence tag-simple sequence repeats (EST-SSRs) were identified with a distribution frequency of 12.5% total unigenes. Out of 8,955 designed EST-SSR primers, 150 primers were selected for the development of potential molecular markers. Among these markers, 17 EST-SSR markers presented a moderate level of genetic diversity among three C. alismatifolia cultivars, one hybrid, three Curcuma, and two Zingiber species. Three different genetic groups within these species were revealed using EST-SSR markers, indicating that the markers developed in this study can be effectively applied to the population genetic analysis of Curcuma and Zingiber species. This report describes the first analysis of transcriptome data of an important ornamental ginger cultivars, also provides a valuable resource for gene discovery and marker development in the genus Curcuma. © 2019, The Author(s).